2016
DOI: 10.3109/00016357.2016.1142113
|View full text |Cite
|
Sign up to set email alerts
|

Income-related inequality in perceived oral health among adult Finns before and after a major dental subsidization reform

Abstract: Objectives In Finland, a dental subsidization reform, implemented in 2001-2002, abolished age restrictions on subsidized dental care. The aim of this study was to investigate income-related inequality in the perceived oral health and its determinants among adult Finns before and after the reform. Materials and methods Three identical cross-sectional nationally representative postal surveys, concerning perceived oral health and the use of dental services among people born before 1971, were conducted in 2001 (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…21-22 Under such circumstances, concerns have been raised about the potential for widening disparities associated with public health programs that are not tailored to high-risk subgroups like CSHCN. 23 The idea is that such programs “skim off the top” by benefitting individuals who are best positioned to take advantage of the program, leaving behind less advantaged program participants. The current data support the concept of widening disparities pertaining to CSHCN in the ABCD Program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21-22 Under such circumstances, concerns have been raised about the potential for widening disparities associated with public health programs that are not tailored to high-risk subgroups like CSHCN. 23 The idea is that such programs “skim off the top” by benefitting individuals who are best positioned to take advantage of the program, leaving behind less advantaged program participants. The current data support the concept of widening disparities pertaining to CSHCN in the ABCD Program.…”
Section: Discussionmentioning
confidence: 99%
“…14 This raises specific concerns about vulnerable child subgroups within ABCD, like CSHCN, because of the potential for programs like ABCD to widen oral health inequalities. 23 …”
mentioning
confidence: 99%
“…A recent Australian study on socioeconomic gradients in toothache prevalence during 1994‐2013 detected two‐ to three‐fold differences in toothache prevalence between the highest and lowest household income tertiles. On the other hand, Finnish studies have found clearly smaller, even minimal, differences in toothache prevalence both by household income and by educational levels among + 30‐year‐olds in the 2000s . However, in both countries, studies found that socioeconomic differences increased during the follow‐up .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Finnish studies have found clearly smaller, even minimal, differences in toothache prevalence both by household income and by educational levels among + 30‐year‐olds in the 2000s . However, in both countries, studies found that socioeconomic differences increased during the follow‐up . It has been found that perceived general health and income itself explained most of the income‐related differences in toothache prevalence in Finland, possibly due to differences in access to oral healthcare services by socioeconomic status .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation